Emergent Archiepiscopal Leadership within the Anglican Communion. Issue 1 (18th March 2015) - Percy, Martyn
Abstract: Each Archbishop of Canterbury has a distinctive style of leadership. To some extent, this will always be shaped and framed by prevalent contemporary cultures of leadership that are to be found within wider society. The paper examines and questions some aspects in the development of the current Archbishop of Canterbury's role. It argues that the combination of a certain kind of charismatic leadership, coupled to enhanced managerial organization, may be preventing the prospect of theological acuity and spiritual wisdom playing a more significant role in the continual formation of ecclesial polity in the Church of England, and across the wider Anglican Communion.